THE NARRATOR IN ALLEYS OF MEMORY - Fernandes de Oliveira, Aciomar (Revista Gênero e Interdisciplinaridade, 2023)
Literature, as an instrument for denouncing reality, is extremely relevant because it allows subjects to reflect on inequalities, discrimination, prejudice existing in our society, and not just an entertainment tool. Conceição Evaristo, being a woman and black, finds in fiction a refuge and, at the same time, a way of showing how the characteristics of a past of pain and suffering reverberate in the present, contributing to exacerbate the social exclusion of black men and women. In this sense, the aim of this article is to discuss the identity construction present in the book Alleys of Memory, by the aforementioned author, based on the analysis of the narrator and the correlation between writing and life present in Evaristo’s text, which she calls escrivivência. To do so, we followed a qualitative methodology, of a bibliographical nature, in which important references on the subject were selected, in addition to analyzes of excerpts from the aforementioned narrative. We conclude this article by inferring that Evaristo’s work represents the voice of minorities who find themselves on the margins of society and, on a daily basis, struggle not only to gain space and recognition, since they are also part of the composition of the national identity; but, above all, out of respect and equality